2002
DOI: 10.1081/rrs-120014619
|View full text |Cite
|
Sign up to set email alerts
|

THE BRET2/ARRESTIN ASSAY IN STABLE RECOMBINANT CELLS: A PLATFORM TO SCREEN FOR COMPOUNDS THAT INTERACT WITH G PROTEIN-COUPLED RECEPTORS (GPCRS)*

Abstract: In BRET2 (Bioluminescence Resonance Energy Transfer), a Renilla luciferase (RLuc) is used as the donor protein, while a Green Fluorescent Protein (GFP2) is used as the acceptor protein. In the presence of the cell permeable substrate DeepBlueC, RLuc emits blue light at 395 nm. If the GFP2 is brought into close proximity to RLuc via a specific biomolecular interaction, the GFP2 will absorb the blue light energy and reemit green light at 510nm. BRET2 signals are therefore easily determined by measuring the ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 0 publications
0
73
0
2
Order By: Relevance
“…To directly quantify the magnitude of ligand-induced arrestin interaction with the NOP receptor, we employed a real-time BRET assay system to measure the direct interaction between NOPR and both arrestin-2 and arrestin-3 (Bertrand et al, 2002). We used transient transfections consisting of the human NOP receptor with the Renilla reniformis luciferase (Rluc) energy-transfer donor fused in frame to the C-terminal domain, together with arrestin-2-Venus or arrestin-3-Venus energy-transfer acceptor proteins (Gimenez et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…To directly quantify the magnitude of ligand-induced arrestin interaction with the NOP receptor, we employed a real-time BRET assay system to measure the direct interaction between NOPR and both arrestin-2 and arrestin-3 (Bertrand et al, 2002). We used transient transfections consisting of the human NOP receptor with the Renilla reniformis luciferase (Rluc) energy-transfer donor fused in frame to the C-terminal domain, together with arrestin-2-Venus or arrestin-3-Venus energy-transfer acceptor proteins (Gimenez et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A better interaction with ␤-arrestin2 over ␤-arrestin1 has been observed for many GPCRs, and these are called class A GPCRs, whereas class B receptors do bind equally well to both ␤-arrestins (and also to visual arrestins; Oakley et al, 2000). BRET-based assays for the GPCR/␤-arrestin interaction are so robust that they are suitable for high-throughput screening (Bertrand et al, 2002;Hamdan et al, 2005), and they have been developed for many receptors (e.g., chemokine, opiate, dopamine, and prostanoid receptors) (Hamdan et al, 2005;Qiu et al, 2007;Coulon et al, 2008;Klewe et al, 2008;Masri et al, 2008;Leduc et al, 2009). The assays also revealed that receptors that undergo ␤-arrestinindependent internalization, such as the gonadotropin releasing hormone receptor, also did not show receptor/␤-arrestin BRET signals (Kroeger et al, 2001).…”
Section: B Binding Of ␤-Arrestinsmentioning
confidence: 99%
“…25,36,37 Compared to BRET1, BRET2 has the advantage of an increased separation between the emission of Rluc and that of GFP2 (110 for BRET2 vs. 50 for BRET1), resulting in a lower background. On the other hand, a major disadvantage of BRET2 is that the luminescence emitted by Rluc upon catalyzing DeepBlueC is much less than its emission when coenterazine-h is used as a substrate.…”
Section: Choice Of Bret Assay For Htsmentioning
confidence: 99%
“…Currently, both BRET versions are being used for studying protein-protein interactions, including monitoring of GPCR activation by BRET-based β-arrestin recruitment assays. 15,[22][23][24][25][26][27][28][29] In this study, we report the development of an optimized BRET1-based β-arrestin2 assay for several GPCRs belonging to class A and class B receptors. Unlike most of the previous BRETbased β-arrestin studies that relied on the transient coexpression of the receptor and β-arrestin, the current work employed double stable cell lines that constitutively expressed optimal levels of both β-arrestin2-Rluc and GPCRs fused to a modified EYFP (VENUS), providing a robust and a mainstreamed platform for HTS of GPCR ligands.…”
mentioning
confidence: 99%